AN URBAN WALKABOUT WITH CINDY SHERMAN'S PHOTOGRAPH, "UNTITLED #466, 2008” - Filippelli, Sandra Elaine (Art/Research International, 2021)
In this article, the narrator of the story immerses herself in the interiority of a character depicted in a Cindy Sherman portrait on an art gallery wall. The narrator invites the character out of the photograph and immerses her in the pandemic-stricken city outside. In this way, the author engages with contemporary visual art while composing fictional text as literary art. Her encounter with the photograph becomes an aesthetic visual and literary investigation of art, text, and characterization set against the backdrop of the global COVID-19 crisis.